Caracterização e diversidade da macrofauna bentônica de praias Amazônicas: Marudá e Sacaiteua, município de Marapanim, Pará - VILHENA, José Geraldo Moraes (2019)
Bentos represents the biota of bottom-bound organisms that interface water with solid materials, consisting of a wide variety of phyla. The beaches of the north coast of Brazil are under the influence of intense rainfall and estuarine waters, which in turn must condition the biotic communities that live in them. This study is part of a project that aims to survey and characterize the benthic fauna of coastal beaches of Marapanim (PA). The present work aimed to conduct a survey of the benthic macrofauna (> 0.5 mm) from two beaches in Marapanim (PA). For this, sediment was collected in the intertidal region in July 2018 (Marudá) and December 2018 (Sacaiteua), both being transition periods (rainy / dry and dry / rainy). To obtain the samples, the spatial demarcation was based on longitudinal transects from the low tide to the high tide mark, on which four to six sampling stations were distributed, depending on the width of the beach. Thus, resulting in five transects with six stations in Marudá, six transects with four stations in Sacaiteua, totaling 54 samples in both beaches. Samples of the macrofauna of the intertidal zone were taken in order to characterize and evaluate the structure of their communities. Sediment temperatures and salinity of interstitial water were also measured at each station and samples were taken for particle size analysis. In Marudá beach, the average temperature presented higher valuesccompared to those recorded for Sacaiteua. Marudá was also more heterogeneous with regard to salinity and pH values. There was a higher presence of silt and the water content was also higher. Differences were significant between seasons of the same beach as well as between beaches, as expected for differences between beaches with different degrees of hydrodynamism. The benthic macrofauna was dominated by annelids and molluscs, as well as small crustaceans. Most of the taxa were found on both beaches, which demonstrates the connectivity of the regional fauna. In Marudá beach, 107 organisms, belonging to 27 taxa and four phyla, were obtained, Annelida (10 taxa), followed by Mollusca (9 taxa), Arthropoda (7 taxa), Nemertea (1 taxon). In Sacaiteua beach, 78 organisms, belonging to 17 taxa and three phyla, were recorded, Annelida (12 taxa), followed by Mollusca (three taxa), Arthropoda (two taxa). In Marudá beach, however, the diversity of groups was greater. In addition to Polychaeta, a significant number of mollusks and crustaceans were found. In Sacaiteua, the diversity of groups was smaller, but there was greater richness of Polychaeta, with smaller number of Mollusca and Crustacea species. Phylum Annelida was the dominant; one species of Nephytiidae being the most important organism in Marudá, while one species of Nereiididae dominated in Sacaiteua. Differences in composition, abundance and ecological parameters can be attributed to the difference in beach location, as less exposed beaches, such as Marudá, allow a better colonization of these extensive sand strips under less water stress. This study broadens the knowledge of benthic macrofauna for the region and demonstrates its relevance in assessing environmental quality. We suggest the need for sampling at other times of the year in order to broaden the characterization of the beach and its biodiversity.